1998
DOI: 10.1177/154193129804200515
|View full text |Cite
|
Sign up to set email alerts
|

Categorization is Difficult: Use of an Electronic Notebook for Organizing Design Meeting Notes

Abstract: The electronic engineering notebook is a pen-based computer tool designed to capture engineering notes and to assist in structuring them to facilitate subsequent information access. Experiments were conducted in which free-form and fixed-form note-taking interfaces were compared with respect to capturing and structuring notes from a design meeting. Suitability of domain-based and user-defined terminologies for semantic structuring was also tested. Results from the experiment confirmed that a free-form interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…They compared three devices-paper, a PDA, and a Tablet PC-to determine what differences arose from the device being used. Gwizdka compared the effect of note-taking and post-labeling interfaces for note capturing and structuring during engineering design meetings, and found that the separation of input areas by category led to problems and that attaching pre-defined labels to free-form notes after the note-taking could cover more key points [8]. Though the process of our experiment was similar to this study, we focused on the rearrangement of lecture notes rather than engineering notes.…”
Section: Related Workmentioning
confidence: 96%
“…They compared three devices-paper, a PDA, and a Tablet PC-to determine what differences arose from the device being used. Gwizdka compared the effect of note-taking and post-labeling interfaces for note capturing and structuring during engineering design meetings, and found that the separation of input areas by category led to problems and that attaching pre-defined labels to free-form notes after the note-taking could cover more key points [8]. Though the process of our experiment was similar to this study, we focused on the rearrangement of lecture notes rather than engineering notes.…”
Section: Related Workmentioning
confidence: 96%